Analisis Nilai Tambah Pengolahan Abon Ikan Tuna di Kelurahan Mata Kecamatan Kendari Kota Kendari (Studi Kasus Industri Rumah Tangga Dzakiyah Permata) - Dzulmawan, Muhammad; Geo, Laode; Gafaruddin, Abdul (Department of Agribusiness, Halu Oleo University, 2019)
The purpose of this research is to analyze the amount of profit and value added that resulted in the processing of tuna fish abon in the household industry